Personality Traits Influencing Young Adults Conspicuous Consumption - Ponce-Arias, H (Blackwell Publishing Ltd, 2021)
Young consumers contribute significantly to the growth of luxury consumption worldwide, particularly in the new-luxury category. Studies addressing personality conditions that influence the consumption of new-luxury brands are still limited. Based on the 3M Model of Motivation and Personality, this study demonstrates that the competitiveness and need for learning personality traits influence bandwagon and snob consumption of new-luxury brands. The main hypotheses establish that bandwagon and snob consumption are affected positively by the competitiveness personality trait and negatively by the need for learning personality trait. Data were collected through a survey responded by 717 college students, representing young adult group and also distributed in five different Chilean cities. The analysis was carried out using structural equation models. The results confirmed that competitiveness predisposed individuals to conspicuous consumption associated with new-luxury brands in the clothing, perfume and smartphone categories. Regarding the need for learning trait, only a negative relationship was found in the clothing category but not in the perfume and smartphone categories. This study contributes to extend our understanding of luxury consumption, providing empirical evidence of the effects of psychological conditions on the consumption of new-luxury goods by young adults. © 2020 John Wiley & Sons Ltd